EmCat-Eng: A catalogue of 1,759 basic emotion terms in English - Bąk, Halszka (Studia Anglica Posnaniensia, 2022)
This study investigates the lexicalization patterns of six basic constructs of emotion in English: anger, disgust, fear, joy, sadness, and surprise. These words, along with all their synonyms in noun, verb, and adjective forms were recorded and supplied with corpus frequency data. The resulting catalogue of basic emotion terms in English was analyzed. The categories of words denoting different emotions were quantified in order to determine their relative cultural significance. Word frequency patterns were analyzed in order to determine any manifestations of display rules. The results indicate that in English all emotions are preferentially lexicalized as adjectives. Negative emotions are preferentially expressed as verbs, and positive emotions – as nouns. English boasts more words for negative than positive emotions, confirming the presence of the negative differentiation effect. At the same time, the less numerous words for positive emotions were found to be more frequently used, confirming the Pollyanna effect. The study revealed the central role of fear in the English-speaking world. Uniquely, fear was found to conceptually and semantically overlap with all other basic emotions regardless of their valence; the mean frequency of all the words denoting fear made it the second most frequent overtly, verbally communicated emotion in English – after joy.